LITERATURE REVIEW: VALIDITY OF E-MODULE DEVELOPMENT IN SENIOR HIGH SCHOOL BIOLOGY LEARNING - Anggriani, Fila Dwi; Arsih, Fitri; Fuadiyah, Sa’diyatul; Rahmi, Fitri Olvia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2024)
Education is something that every person needs. Education can be interpreted as an effort to make oneself better. The most important person in the learning process is the teacher, because they are responsible for planning, implementing and evaluating student learning outcomes. Providing more interesting and innovative teaching materials to support learning is oneway teachers can make classes active and interactive. Electronic modules (e-modules) can be adapted to students' needs and used for independent learning anytime and anywhere. E-modules are an independent teaching material for students which are arranged systematically and interestingly. The data collection technique used in this literature review was carried out by collecting similar articles that had been published in online journals via Google Scholar and Google Scholar. Based on the analysis of the e-module validity test, it was found that the average overall validity value of e-module teaching materials was 93.71% with very valid criteria. Based on the results of the meta-analysis, it can be concluded that the development of e-modules in high school biology learning has met the very valid category in terms of content, language, presentation and graphics so that this e-module can be used by teachers and students.